Dynamic Origin of Evolution and Social Transformation - Kirilyuk, A.P. (Наносистеми, наноматеріали, нанотехнології, 2013)
We analyse the unreduced, nonperturbative dynamics of an arbitrary manybody
interaction process by means of the generalised effective potential
method and reveal the well-specified universal origin of change (emergence),
time and evolution in an a priori conservative, time-independent system. It
appears together with the universal dynamic complexity definition, where
this unified complexity conservation and transformation constitute the essence
of evolution. We then consider the detailed structure of this universal
evolutionary process showing its step-wise, ‘punctuated’ character, now provided
with the exact mathematical description. Comparing the expected features
of a revolutionary complexity transition near a step-like complexity
upgrade with the currently observed behaviour of world’s social and economic
systems, we prove the necessity of complexity revolution towards the superior
civilisation level of well-defined nature, the only alternative being an
equally dramatic and irreversible degradation, irrespective of efforts applied
to stop the crisis at the current totally saturated complexity level. Ми аналізуємо нередуковану, непертурбативну динаміку довільного процесу взаємодії багатьох тіл за допомогою узагальненої методи ефективного потенціалу і розкриваємо точно визначене універсальне походження
зміни (виникнення), часу та еволюції в апріорі консервативній, незалежній від часу системі. Вона з’являється разом з визначенням універсальної
динамічної складності, згідно з яким збереження та перетворення цієї
уніфікованої складності і створюють еволюцію. Далі ми розглядаємо детальну структуру цього універсального еволюційного процесу, яка демонструє східчастий, переривистий характер, споряджений тепер точним математичним описом. Порівнюючи очікувані особливості революційного
переходу складності біля її східчастого підвищення з сучасною поведінкою світових суспільних та економічних систем, ми доводимо необхідність революції складності до вищого рівня цивілізації добре визначеної
природи, з єдиною можливою альтернативою такої ж драматичної та необоротньої деґрадації, незалежно від зусиль, які докладаються для подолання кризи на сучасному, цілком насиченому рівні складності. Мы анализируем нередуцированную, непертурбативную динамику произвольного процесса взаимодействия многих тел с помощью обобщённого
метода эффективного потенциала и выявляем хорошо определённую универсальную природу изменения (возникновения), времени и эволюции в
априори консервативной, независящей от времени системе. Она обнаруживается вместе с определением универсальной динамической сложности, сохранение и преобразование которой и составляют сущность эволюции. Мы затем рассматриваем детальную структуру этого универсального
эволюционного процесса, демонстрирующую ступенчатый, прерывистый
характер, снабжённый теперь точным математическим описанием. Сравнивая ожидаемые особенности революционного перехода сложности
вблизи её ступенчатого роста с наблюдаемым сейчас поведением мировых
общественных и экономических систем, мы доказываем необходимость
революции сложности к высшему уровню цивилизации хорошо определённой природы, с единственной возможной альтернативой столь же драматической и необратимой деградации, независимо от усилий, прилагаемых для преодоления кризиса на текущем, полностью насыщенном
уровне сложности.